CONFORMITY ASSESSMENT OF UKRAINIAN TEXTILES (Development Service Industry Management, 2024)
The article considers the issues of assessing the compliance of textile products of Ukrainian origin with the current regulatory documents. Ukraine is facing a problem with textiles accounting for up to 10% of total waste. The quality of textile materials and products is an integral part of responsible production and consumption. An analysis of the life cycle of textiles shows that they reach a point where they cannot be resold, reused, repaired, restored, recycled or reused. Therefore, textile recycling is a prerequisite and is crucial for turning waste into value.Linen napkins of Ukrainian production were chosen as the object of study. Modern methods were used to conduct the research: light microscopy, gas chromatography, determination of the content of extractable heavy metals using an atomic emission spectrophotometer with inductively coupled plasma.The quality and safety indicators of napkin samples, the mass fraction of raw material components, pH, pesticide content, and the content of extracted heavy metals were studied. The component composition of the samples did not correspond to the napkin labelling. Based on the established indicators, the pH level (5.3), the content of pesticides and extracted heavy metals (quantitative characteristics do not exceed the sensitivity of the device and comply with regulatory documents), a conclusion was made about the safety level of napkins. Conclusions are drawn about the activities of Ukrainian textile producers in promoting their products and responsible consumption. The current requirement is the development of ‘green’ passports for textile products, indicating the composition of the fabric (content of recycled fibres), the origin of the material, and available processing methods. It is advisable to continue the practice of harmonising Ukrainian standards with EU standards and not to weaken state supervision in confirming compliance.
Keywords: quality; safety; conformity assessment; technical regulation; textiles